Comparison of a Tumor-Ratio–Metastasis Staging System and the 8th AJCC TNM Staging System for Gastric Cancer - Zhang, Miaoquan; Ding, Chao; Xu, Lin; Ou, Biyi; Feng, Shoucheng; Wang, Guoqiang; Wang, Wei; Liang, Yao; Chen, Yingbo; Zhou, Zhiwei; Qiu, Haibo (Frontiers in Oncology, 2021)
Background: The 8th edition American Joint Committee on Cancer (AJCC) TNM staging system has been widely used, but might cause staging migration. In present study, we intended to evaluate the prognostic value of the lymph node ratio (LNR) and establish a novel tumor–ratio–metastasis (TRM) staging system. Method: A total of 15,206 gastric cancer patients including 2,032 from Sun Yat-sen University Cancer Center and 13,174 from the US Surveillance, Epidemiology, and End Results (SEER) database were enrolled in the present study. A training set (Group1, 2,032 patients) was classified into 5 LNR categories, and a novel TRM staging system was constructed. We compared overall survival (OS) between TRM and TNM systems, and the analysis was repeated in a validation set (Group2, 13,174 patients). Result: Optimal LNR cut points divided patients into 5 categories: LNR0: 0%; LNR1:0%< LNR≤10%; LNR2: 10%< LNR≤25%; LNR 3a:25%< LNR≤60%; LNR 3b: LNR >60%. In univariate analysis, the log-rank x2 of LNR stage (group 1/2: x2=463.1/2880.8) was larger than that of pN stage (group 1/2: x2=281.5/2240.8). In univariate and multivariate Cox regression, the Wald x2 and hazard ratio (HR) 95% CI of each LNR stage was larger than that of pN stage. In stratified analyses, by using Kaplan-Meier method, significantly heterogeneous OS was found in every pN category but in one of LNR category. Conclusion: TRM staging system showing a better homogeneity and discriminatory ability could better predict the prognosis of GC patients than TNM staging system, which could be considered as a substitution for TNM staging system.